2017
DOI: 10.1002/gch2.201700084
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Numerical Study on Piezoelectric Energy Harvester for Self‐Powered Pacemaker Application

Abstract: The potential application of this energy harvesting has been recognized in the form of the replacement of batteries of the pacemakers. Since the Ni-Cd or Li-ion batteries used for pacemakers have finite life span [15] and hence these require replacement after a certain period. To overcome this drawback, researchers have been exploring methods where an energy harvester could scavenge energy from human body and power the pacemaker.Goto et al. [16] carried out the pioneering work in the field of powering leadless… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Among all of these routes, mechanical movement of organs is the most abundant energy source in vivo. Self-powered IMEDs harvesting biomechanical energy from cardiac motion 2224 , respiratory movement, and blood flow is part of a paradigm shift that is on the horizon 25 . A triboelectric nanogenerator (TENG) 26 has been developed as a potential biomechanical energy harvester for self-powered IMEDs 27 , which shows many unique advantages, such as flexibility, desirable biocompatibility, and light weight, in implantable applications 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Among all of these routes, mechanical movement of organs is the most abundant energy source in vivo. Self-powered IMEDs harvesting biomechanical energy from cardiac motion 2224 , respiratory movement, and blood flow is part of a paradigm shift that is on the horizon 25 . A triboelectric nanogenerator (TENG) 26 has been developed as a potential biomechanical energy harvester for self-powered IMEDs 27 , which shows many unique advantages, such as flexibility, desirable biocompatibility, and light weight, in implantable applications 28 .…”
Section: Introductionmentioning
confidence: 99%
“…The values of voltage and electric current obtained in this study are similar to several studies on the use of piezoelectric to produce energy. In this study, the average measured voltage and current values were 17.58-29.85 V, and the average measured electric current was 1.16-2.01 mA, while several studies showed that the voltage and electric current generated by the piezoelectric were 5.08 V and 10.2 mA [24], 3.5 V and 100 mA [25], 4 V and 0.015 A [26], 2.3 mV [27], and 0.9 V [28].…”
Section: Resultsmentioning
confidence: 99%
“…For example, in [105], the authors propose a prototype design for energy harvesting in roadway pavements using the vibration produced by vehicles passing from speed bumps. Kinetic energy from human, e.g., energy from heart-beats [106], is also used to generate energy.…”
Section: Kinetic Energy Sourcesmentioning
confidence: 99%